Design of gain schedule fractional PID control for nonlinear thrust vector control missile with uncertainty. (2nd October 2018) - Ahmed, Mohamed Fawzy; Dorrah, Hassen Taher
ABSTRACT: The purpose of this paper is to control the trajectory of the nonlinear missile model in the pitch channel by using Fractional PID controller ( FPID ) and Gain Schedule Fractional PID controller ( GSFPID ). FPID and GSFPID with nonlinear missile model are designed where their parameters are tuned by Simulink design optimization in the Matlab toolbox. This optimization method gives the optimal parameters that achieve the best tracking with step unit reference signal. The GSFPID controller compensates the restrictions that represent physical limits of actuators in the pitch channel. The GSFPID with nonlinear missile model is designed in two phases. The first phase is the boost phase where the thrust force is maximized and the second phase is sustain phase where the thrust force is minimized. The equations of motion for nonlinear missile model with FPID and GSFPID are modelled mathematically in the Matlab-Simulink environment. The results of FPID and GSFPID controllers with the nonlinear missile model are presented and compared. The wind effect and the dynamic uncertainties effects are researched and the results are compared. The closed-loop nonlinear system is linearized by the Simulink linear analysis tool at critical operating point t = 5 . 8 sec and the stability is studied.